RETRACTED: Exosomes Derived From MicroRNA-148b-3p-Overexpressing Human Umbilical Cord Mesenchymal Stem Cells Restrain Breast Cancer Progression - Yuan, Lei; Liu, Yuqiong; Qu, Yunhui; Liu, Lan; Li, Huixiang (Frontiers in Oncology, 2019)
Exosomes derived from human umbilical cord mesenchymal stem cells (HUCMSCs) expressing microRNAs (miRs) have been highlighted as important carriers for gene or drug therapy. Hence, this study aimed to explore the role of exosomal miR-148b-3p from HUCMSCs in breast cancer. Clinical samples subjected to RT-qPCR detection revealed that miR-148b-3p was poorly expressed, while tripartite motif 59 (TRIM59) was highly expressed in breast cancer tissues. Online analyses available at miRanda, TargetScan and miRbase databases revealed that miR-148b-3p could bind to TRIM59, while dual-luciferase reporter gene assay further verified that TRIM59 was a target gene of miR-148b-3p. Next, miR-148b-3p mimic or inhibitor and siRNA against TRIM59 were delivered into the breast cancer cells (MDA-MB-231) to alter the expression of miR-148b-3p and TRIM59 so as to evaluate their respective effects on breast cancer cellular processes. Evidence was obtained demonstrating that miR-148b-3p inhibited cell proliferation, invasion and migration, but promoted cell apoptosis in breast cancer by down-regulating TRIM59. Next, MDA-MB-231 cells were co-cultured with the exosomes derived from HUCMSCs expressing miR-148b-3p. The results of co-culture experiments demonstrated that HUCMSCs-derived exosomes carrying miR-148b-3p exerted inhibitory effects on MDA-MB-231 progression in vitro. In vivo experimentation further confirmed the anti-tumor effects of HUCMSCs-derived exosomes carrying miR-148b-3p. Taken together, HUCMSC-derived exosomes carrying miR-148b-3p might suppress breast cancer progression, which highlights the potential of exosomes containing miR-148b-3p as a promising therapeutic approach for breast cancer treatment.